TANGGUNG JAWAB PERAWAT DALAM MELAKUKAN TINDAKAN MALPRAKTIK - Dewi Harmoni; Rudi Erwin Kurniawan; Nuzul Abdi Makhrifatullah (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Nurses are an important part in health development. Nurses are also part ofhealth workers, even in the implementation of health services nurses play avery important role, because in their daily life they are always in directcontact with patients and other health workers. Nurses in health serviceslegally cannot provide services because they must obtain permission from thegovernment which is stated in Law No. 36 of 2006 Article 23 paragraph 3 concerning health, moral encouragement from nurses as health workers isdesired by the community to provide health services to the community. inremote areas which are generally difficult to reach and even met by doctors,so that eventually nurses provide health services to the community, but on theother hand, this can be blamed because nurses provide health services withoutpermission from the government which can also be called (malpractice). ) theauthor is interested in reviewing and discussing how the legal arrangementsregarding the position of nurses in Indonesia and how criminal responsibilityfor nurses who commit malpractice acts. This research was conducted with anormative legal research type, the type of statute approach research, namelythe approach to legislation that focuses on primary legal materials thatregulate malpractice crimes against nurses. Lack of public understanding andempathy from nurses themselves who think nurses can act like doctors Theimplementation of nursing practice by nurses who are not in accordance withthe regulations and legislation will clearly be very detrimental to the servicerecipients and the nurses themselves. If someone complains or even questionsit legally, it will have legal consequences for the nurse herself.